Electrical design of Panasiatic Call Center Building in Bacolod City - Bravo, Jeffrey B. (Manila Professional Regulation Commission, 2015)
Panasiatic call center Building was constructed solely for the purpose that it will be rented by Panasiatic Solutions, a call center business company. The electrical system design of this building will start from indoor lighting calculations using the Lumen or Zonal Cavity Method. Accurate indoor lighting system design will provide sufficient light for the performance of the visual task to enable the person to do these tasks efficiently and accurately and at the same time to create a comfortable environment with a minimum of eyestrain and fatigue. It also promotes safety by preventing accidents often cause by poor visibility. Electrical engineering calculations were based on the provisions of Philippine Electrical Code 2009 pertaining to the requirements and electrical energy needs of Panasiatic Solutions.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-662G donated by Mr. Jaime E. Mendoza.
Keywords: Buildings -- Electric equipment